-12 + 2a = -6 (1+a)?
Answer is 0 = 6
Answer:
D) 1
Step-by-step explanation:
using the distributive property we have ax+a+bx-b-2=0. because the equation is true for all real x, ax=-bx. this means a-b-2=0 and a=-b. a-b-2=0 becomes a=b+2. then we substitute a for -b and get -b=b+2 which becomes 2b=-2 so b=-1. since a=-b, a=1
Hi there!
For the Pythagorean Theorem, basically you just need to apply this formula: a^2 + b^2 = c^2
And then find the root of the hypotenuse.
For example,
15^2 + 8^2 = the hypotenuse^2
Which equals, 225 + 64 = 289
Square root of 289 = 17
Please mark me brainliest if this helps!
Have a wonderful day!
The slope intercept formula is:
y = mx + b
m is the slope
b is the y-intercept
We know:
Slope (m) is -4
y-intercept (b) is -1
All you need to do is plug these numbers into the slope intercept formula given above!
y = -4x - 1
Hope this helped!
~Just a girl in love with Shawn Mendes